Revealing the Role of Sharia Banking and Marketing Strategy in Halal Food and Beverage Industry - Gema Sri Basyir; Lalu Takdir Jumaidi (Cita Konsultindo Research Center, 2024)
This study aims to explain and provide a description of the role of Islamic banking and marketing strategies in the halal food and beverage industry in Central Lombok, West Nusa Tenggara. The research paradigm employed is interpretive and phenomenological in its approach. The data collected for this study is primarily through interviews and documentation. The analysis is conducted using noema, epoche, noesis, intentional analysis, and eidetic reduction. The research findings reveal that the confidence of the stakeholders can determine the necessary steps to be taken. The owners of Sasak Aren MSMEs do not yet desire to increase their capital through Sharia banks due to existing perspectives that do not align with their beliefs, despite the bank's adherence to Sharia principles. Moreover, these businesses are still classified as small. Thus, the role of Sharia banking in Sasak Aren MSMEs is currently limited to promotion. Despite their small scale, these MSMEs have complete certification, notably the halal certification, which is utilized as one of the marketing strategies for product development.